The role of agriculture in regional development - Harsányi, Endre; Nagy, Orsolya; Harsányi, Gergely; Nagy, János (Acta Agraria Debreceniensis, 2014)
Agriculture is the leading national economic sector of Hajdú-Bihar county. The proportion of employees in this sector and the share of pro ducts produced in this region is above the country average. The contribution of agriculture to the GDP is 6.3%, as opposed to the average value of the country (3.3%). Based on their primary activity, 8% of the enterprises in the county are classified as agricultural and forestry companies, while this proportion is only 5.3% in the whole country. Nearly three quarters (71.1%) of the sowing area is occupied by maize and other cereals, mainly wheat. This proportion is slightly more than the country average (69.2%). The proportional area of oil crops - including sunflower – and roughage is nearly the same as the country average. However, there is a significant difference in vegetable production. Due to the higher intensity of vegetable production, the area occupied by vegetables is three times the country average. 19.4% of the crop products, 23.5% of animal products and living animals, 25.8% of the income generated by production factors and 29.8% of net enterprise income of Hungary originates from the North Great Plain region. The facilitation of creating local markets, e.g. local public food supply, satisfying the needs of food trade with local goods, the necessary awareness raising actions, secondary and higher education of experts, as well as the more specific and targeted utilisation of development resources are agricultural development tasks.